616. Patients Experiencing Homelessness and Opioid Use Disorder with Infectious Complications Treated with OPAT at Medical Respite: Evaluation of Retention in Care at 30 days and Role of Addictions Consultation. (31st December 2020) - Beieler, Alison M; Beieler, Alison M; Klein, Jared W; Bhatraju, Elenore; Iles-Shih, Matthew; Enzian, Leslie; Dhanireddy, Shireesha; Dhanireddy, Shireesha
Abstract: Background: Patients experiencing homelessness and opioid use disorder (OUD) admitted for severe infections often require prolonged hospital stays. These patients, typically evaluated by Infectious Disease (ID) providers, are often excluded from Outpatient Parenteral Antimicrobial Therapy (OPAT) due to social risk factors. Medical respite, near Harborview Medical Center (HMC), offers a supportive environment for patients to receive OPAT with daily nurse administered antibiotics. For further support, our institution created a dedicated Addiction medicine consult service March 1, 2019 to assist with initiation of medications for opioid use disorder (MOUD) and linkage to outpatient care for interested patients. Methods: We performed retrospective review of all patients > 18 years with OUD admitted for procedure/inpatient stay from 1/31/2018 – 1/31/2020 who discharged to medical respite for OPAT. The minimum follow up period was 90 days. We recorded demographics, OUD history, diagnosis, discharges against medical advice (AMA), and total readmissions. We evaluated outcomes of 4 care interventions (ID consult, Addiction consult, linkage to case management and/or mental health, linkage to MOUD) in relation to successful OPAT completion, clinical cure, and retention in MOUD at 30 days. Results: Fifty-three patients had 63 OPAT episodes of care (Table 1). Median length of stay (LOS) was 19 days inpatient, and 33 days at medical respite. Common diagnosis included, osteomyelitis 46 (73%), bacteremia 27 (43%), septic joint 17 (27%), epidural abscess 10 (16%), and endocarditis 10 (16%). There were 24 OPAT episodes which received all 4 interventions (Table 2). Episodes during which 4 interventions occurred were more likely to result in clinical cure (p = 0.03) and retention in MOUD treatment at 30 days (p = 0.003) compared to episodes where 3 or fewer interventions occurred (Table 3). Table 1. Demographics Table 2. OPAT Care Interventions, n =63 Table 3. Summary of Outcomes, n =63 Conclusion: Patients discharged to medical respite who received the combination of ID consult, Addiction consult, case management and/or mental health, and MOUD had higher rates of clinical cure compared to those who did not receive all four interventions. Developing a patient-centered comprehensive care plan, including ongoing support and access to MOUD should be a priority to ensure successful treatment of infections. Disclosures: All Authors : No reported disclosures